Tyro3-mediated phosphorylation of ACTN4 at tyrosines is FAK-dependent and decreases susceptibility to cleavage by m-Calpain. (February 2018) - Shao, Hanshuang; Wang, Anna; Lauffenburger, Douglas; Wells, Alan
Abstract: Tyro3, a member of TAM receptor tyrosine kinase family, has been implicated in the regulation of melanoma progression and survival. In this study, we sought the molecular mechanism of Tyro3 effects avoiding endogenous background by overexpression of Tyro3 in fibroblasts that have negligible levels of Tyro3. This introduction triggers the tyrosyl-phosphorylation of ACTN4, a member of actin binding protein family involved in motility, a behavior critical for invasive progression, as shown by siRNA to Tyro3 limiting melanoma cell migration and invasion. Tyro3-mediated phosphorylation of ACTN4 required FAK activation at tyrosine 397 and the EGF receptor cascade, but not EGFR ligand binding. Using PCR-based mutagenesis, the sites of Tyro3-mediated ACTN4 phosphorylation were mapped to ACTN4 tyrosine 11 and 13, and this occurs in conjunction with EGF-mediated phosphorylation on Y4 and Y31. Interestingly, Tyro3-mediated phosphorylation only slightly decreases the actin binding activity of ACTN4. However, this rendered the phosphorylated ACTN4 resistant to the m-calpain cleavage between Y13 and G14, a limited proteolysis that prevents growth factor regulation of ACTN4 interaction with F-actin. Overexpression of both WT ACTN4 and ACTN4Y11/13E, a mimic of ACTN4 phosphorylated at tyrosine 11 and 13, in melanoma WM983b cells resulted in a likely mesenchymal to amoeboidal transition. ACTN4Y11/13E-expressing cells were more amoeboidal, less migratory on collagen I gel coated surface but more invasive through collagen networks. In parallel, expression of ACTN4Y11/13E, in ACTN4 knockdown melanoma WM1158 cells resulted in an increase of invasion compared to WT ACTN4. These findings suggest that Tyro3-mediated phosphorylation of ACTN4 is involved in invasion of melanoma cells.